Peran Zakat Produktif dalam Pemberdayaan Ekonomi Mustahiq (Studi Kasus Lembaga Amil Zakat Dompet Dhuafa Republika Yogyakarta 2017) - Richa Angkita Mulyawisdawati; Imas Rosi Nugrahani (Universitas Alma Ata, 2019)
Indonesia with a majority Muslim population has a large zakat potential. Consumptive zakat distribution will only make mustahiq as recipients. Required distribution of zakat productively to empower mustahiq in order to improve its economy to become muzakki. Productive zakat management carried out by an agency or professional amil zakat institutions, such as the Amil Zakat Dompet Dhuafa Republika Yogyakarta that has been instrumental not only in the country but also abroad. This study aims to determine the role of zakat productive economic empowerment mustahiq in Amil Zakat Dompet Dhuafa Republika Yogyakarta 2017. This research is a descriptive qualitative study using the methods of observation, interview and documentation. Data were analyzed using three inductive data analysis process is the process of data reduction, data presentation and conclusion. The results of this study stated that the role of zakat productive economic empowerment mustahiq in Amil Zakat Dompet Dhuafa Republika Yogyakarta is through the provision of programs of economic empowerment that funds be taken from the fund of productive zakat, the program Kampung Ternak and Institute Mentas Unggul, as well as the provision of socialization, counseling, motivation and ongoing coaching for partners who are being empowered. The program had a positive impact for the economic empowerment mustahiq. Keywords:Zakat Productive, Economic Empowerment, Mustahiq